2011
DOI: 10.4102/sajems.v14i3.193
|View full text |Cite
|
Sign up to set email alerts
|

Consumer awareness and usage of islamic banking products in South Africa

Abstract: This paper investigates the level of consumer awareness and use of Islamic banking products in South Africa. A non-probability sampling method was used whereby a questionnaire was administered to 250 respondents and statistically analysed to determine the factors that are important in the choice between Islamic or conventional banks. It was found that Muslims are aware of Islamic banks, but their rate of use is low, as Muslim customers regard efficiency, lower bank charges, the availability of automatic teller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 25 publications
3
46
0
Order By: Relevance
“…Saini et al (2011) found for South Africa that Muslims are aware of IBs but comparing to their awareness the rate of use is not high. The factors Muslim customers consider important are efficiency, lower bank charges, the availability of ATMs and extensive branch network.…”
Section: Malaysiamentioning
confidence: 99%
See 1 more Smart Citation
“…Saini et al (2011) found for South Africa that Muslims are aware of IBs but comparing to their awareness the rate of use is not high. The factors Muslim customers consider important are efficiency, lower bank charges, the availability of ATMs and extensive branch network.…”
Section: Malaysiamentioning
confidence: 99%
“…IBs should not overemphasize and rely on religious factor as a strategy for more customer attraction. (Haron, Ahmad, & Planisek, 1994;Saini, Bick, & Abdulla, 2011) Sharia approval is a prerequisite of IB for caring Muslim customers only while non-Muslims or some other Muslims might even not require it when they choose their banks. Those customers requiring Sharia approval in the activities of IB will probably be not satisfied with only Sharia approval and require some other qualities endogenous in their IB.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that have sought to investigate Islamic banking issues focused mainly on developing the banking products for Islamic corporate clientele (Ackermann & Jacobs, 2008), consumer awareness and usage of Islamic banking products in South Africa ( Hafsa Orhan Åström, 2013;Saini, Bick & Abdulla 2011) and the legislative challenges (Suleman 2011). Rarely does one find studies that have followed up to report on the impact of these Islamic banking products on entrepreneurship motivation, firm competitiveness and SME performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, this alternative banking method which complies with Islamic economic law (Vawda, 2013) is still considered an emerging market (Dusuki & Abdullah, 2007). It is not well known by many people in the country (Saini, Bick & Abdulla, 2011). A lack of awareness has led to misconceptions surrounding Islamic banking (Cheteni, 2014).…”
mentioning
confidence: 99%